Constitutive analysis of electrically-assisted tensile deformation of CP-Ti based on non-uniform thermal expansion, plastic softening and dynamic strain aging. (July 2017) - Lee, Taekyung; Magargee, James; Ng, Man Kwan; Cao, Jian
Abstract: Electrically-assisted (EA) deformation has shown promising effects in increasing formability and reducing springback in sheet metal forming. This work experimentally and analytically investigated the influence of non-uniform and transient Joule heating on the plastic flow stress of titanium which evolved nonlinearity with time and deformation. Three-stage constitutive analysis was carried out in the present study. First, the pure influence of non-uniform Joule heating was investigated in terms of linear elastic thermal expansion, which then explained the measured drops in stress. Second, the Johnson-Cook model was adopted to interpret a plastic thermal-mechanical behavior of the material loaded at a constant quasi-static deformation rate under the uniaxial tension combined with a single pulse of electric current. Finally, it was revealed that the sudden change in strain rate and rapid heating rate due to an electric current pulse could give rise to the transient occurrence of dynamic strain aging (DSA) in materials. This resulted in an accumulated plastic strain as well as transient high-temperature strain hardening, which estimated the experimentally measured data well. The DSA contribution revealed in this work could help to explain many observations in the past studies in the field of EA deformation. Highlights: The model incorporates the non-uniform Joule heating. Modeled the response from a single electrical pulse, paved the foundation for future multi-pulse cases. Dynamic strain aging due to rapid change in strain rate and heating rate in the case of single-pulse case is modeled. Fine experimental measurement of strain change in the single-pulse case is presented.